Perencanaan Sistem Drainase Guna Mitigasi Bajir pada Taman Impian Jaya Ancol - Munir, Mohamad Husin; Putra, Fisika Prasetyo (Jurnal Kajian Teknik Sipil, 2021)
ABSTRACTSpecial areas have a closed drainage system (existing drainage) when it rains there are still lots of puddles or runoff from the drainage that is not able to accommodate rainwater when it rains continuously, such as the incident in 2019 the Ancol Dreamland Park area could not accommodate rainwater. for a long time so that the Dream Park area flooded. The purpose of this study was to determine the planned rainfall, flood discharge, channel dimensions, and increase the water catchment area in the Ancol Dreamland Park area. The method used is by using Geopore ITB material. The results of this study showed that Q hydrology < Q Hydraulics Daily rain height plans for return periods of 2, 5, 10, 25, 50, and 100 years are 177.78 mm, 339.07 mm, 478.83 mm, 695.42 mm, 887.36 mm, 1107.69 mm and changes flow coefficient of 0.47 m3/s with channel dimensions 90 x 100 cm. to increase the water catchment area there are 13 channels throughout the Ancol Dreamland Park. So it can be concluded that flood control is carried out with 3 alternatives, namely changing channel dimensions, planning to change the flow coefficient, changing channel dimensions and geopore planning. Keywords: Drainage System, Geopori  ITB